1995
DOI: 10.1068/p241059
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Accuracy of Age Estimates of Unfamiliar Faces

Abstract: Abstract. Factors affecting the accuracy with which adults could assess the age of unfamiliar male faces aged between 5 and 70 years were examined. In the first experiment twenty-five 'young' adult subjects, aged 16-25, and twenty-five 'old' adults, aged 51-60, were used. Each subject saw five versions of three different faces: these consisted of an original version of each face and four manipulated versions of it. The manipulations consisted of mirror reversal, pseudo-cardioidal strain, thresholding, and elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
6
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 15 publications
9
113
6
1
Order By: Relevance
“…This decreasing of accuracy of age estimation with ageing is reported in numerous studies on face (e.g. : George & Hole, 1995) and voice (e.g. : Huntley et al, 1987;Moyse et al, 2014).…”
Section: Age Of Participantsmentioning
confidence: 97%
See 1 more Smart Citation
“…This decreasing of accuracy of age estimation with ageing is reported in numerous studies on face (e.g. : George & Hole, 1995) and voice (e.g. : Huntley et al, 1987;Moyse et al, 2014).…”
Section: Age Of Participantsmentioning
confidence: 97%
“…The literature of faces has shown that local (e.g., mouth, nose, eyes) and global features (e.g., skin texture, head shape) could have an impact on age estimation (Burt & Perrett, 1995;George & Hole, 1995, 1998. Different perceptual features of voices (e.g., pitch, quality, articulation, and rate of speech) have also been shown to be strong predictors of age perceived (Harnsberger, Shrivastav, Brown, Rothman, & Hollien, 2008;Hartman, 1979).…”
Section: Accuracy Of Age Estimationmentioning
confidence: 99%
“…Studies involving stimulus manipulation and subjective reports have revealed that specific age-sensitive facial features including the eye region are important in judging facial qualities such as age (George and Hole 1995;Rexbye and Povlsen 2007;Valentine et al 2004). Facial stimulus manipulation, while important to research control, can result in distorted face images that introduce salience artifacts that may not accurately capture the natural perceptual processes associated with age and attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the perception and estimation of age have been carried out using facial images [4][5][6][7][8]. One of the topics addressed in such studies is the accuracy of age estimation.…”
Section: Previous Workmentioning
confidence: 99%